2022
DOI: 10.1186/s13054-022-04071-4
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis subphenotyping based on organ dysfunction trajectory

Abstract: Background Sepsis is a heterogeneous syndrome, and the identification of clinical subphenotypes is essential. Although organ dysfunction is a defining element of sepsis, subphenotypes of differential trajectory are not well studied. We sought to identify distinct Sequential Organ Failure Assessment (SOFA) score trajectory-based subphenotypes in sepsis. Methods We created 72-h SOFA score trajectories in patients with sepsis from four diverse intensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…reported a group of sepsis subtypes based on trajectory clustering, which revealed the alteration of their organ function levels over time. 33 Further studies exploring the evolutionary relationship between the CCI subphenotype we identified and the other acute critical illness with the related subphenotypes are warranted in the future.…”
Section: Discussionmentioning
confidence: 92%
“…reported a group of sepsis subtypes based on trajectory clustering, which revealed the alteration of their organ function levels over time. 33 Further studies exploring the evolutionary relationship between the CCI subphenotype we identified and the other acute critical illness with the related subphenotypes are warranted in the future.…”
Section: Discussionmentioning
confidence: 92%
“…Transcriptomic features that classify the host immune response will contribute to the development of novel therapeutic treatments the improvement of personalized management for sepsis (27). Prediction of clinical outcomes could be well accomplished by establishing the specific classifiers, which have been validated with transcriptomic data (28)(29)(30). Therefore, the purposes of the research were to reveal the clinical subtypes using large-scale samples with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…With the learned K -dimensional topic loading vector for n -th patient θ n , we applied the hierarchical agglomerative clustering method with Euclidean distance calculation and Ward linkage criterion 38 to derive subphenotypes as patient clusters. For determining the optimal number of clusters (subphenotypes), according to Su et al 39 and Xu et al 40 , we applied the NbClust R package 41 , which includes 21 cluster indices to evaluate the quality of clusters. With the patients from the INSIGHT and OneFlorida+ CRN, 13 and 12 out of the 21 indices agreed that four is the optimal number of clusters (Supplementary Table 12 ).…”
Section: Methodsmentioning
confidence: 99%